1999
DOI: 10.1177/016001799761012190
|View full text |Cite
|
Sign up to set email alerts
|

Regional Convergence in Productivity and Productive Structure: The Spanish Case

Abstract: This article analyzes the evolution of regional differences in Spain and emphasizes the importance of a disaggregate analysis at a sectoral level. In particular, the authors observe convergence in productivity at the aggregate regional level but not at the sectoral level. Aggregate convergence seems to be due to the gradual homogenization of regional productive structures. This result may modify some of the conclusions drawn in the recent literature regarding the mechanisms that have generated convergence. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 16 publications
(8 reference statements)
3
38
0
9
Order By: Relevance
“…Convergence is rarely found at a disaggregate level. From a theoretical point of view, such structural effects are not often highlighted as convergence or divergence factors in the literature (Paci and Pigliaru 1999;Cuadrado et al 1999;Esteban 2000;Landesmann and Stehrer 2001). However, Echevarria (1997) shows that a modified version of the Solowian framework can generate such phenomena and more generally can link growth and structural change.…”
Section: Impacts Of Cross-sectoral Labor Reallocationsmentioning
confidence: 99%
“…Convergence is rarely found at a disaggregate level. From a theoretical point of view, such structural effects are not often highlighted as convergence or divergence factors in the literature (Paci and Pigliaru 1999;Cuadrado et al 1999;Esteban 2000;Landesmann and Stehrer 2001). However, Echevarria (1997) shows that a modified version of the Solowian framework can generate such phenomena and more generally can link growth and structural change.…”
Section: Impacts Of Cross-sectoral Labor Reallocationsmentioning
confidence: 99%
“…Some work has been done regarding regional convergence (e.g. Cuadrado-Roura et al 1999, Guerrieri and Iammarino 2003, Longhi and Musolesi 2007; others investigate the interrelationship between structural convergence and income convergence (Wacziarg 2001, Imbs andWacziarg 2003), productivity convergence (Fagerberg 2000, Gugler andPfaffermayr 2004), and monetary integration (Brülhart 1998). Others again focus on the economic catch-up and structural assimilation of countries, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Islam (1995) proposed to set up convergence analyses in a panel data framework where it is possible to control for individual-specific, time invariant characteristics of countries (like the initial level of technology) using fixed effects. Panel data convergence studies using the least squares dummy variable (LSDV) procedure (for countries Knight et al 1993, Islam 1995, for regions de la Fuente 1996, Cuadrado-Roura et al 1999 found extremely fast convergence rates of up to 20 per cent. More recent studies account for the fact dynamic panel data models -as panel convergence models inevitably are -require a different estimation technique than the LSDV estimator.…”
Section: Introductionmentioning
confidence: 99%